Alignment of Local Wisdom Values with Islamic Law in the Tradition of the Peta Kapanca Ceremony - Yono Yono; Amrin Amrin; Ade Irma Imamah (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2022)
This research aimed to examine the alignment of local wisdom values ​​with Islamic law in the tradition of the Peta kapanca ceremony in the Ambalawi sub-District. This study used a descriptive qualitative type with a phenomenological and sociological approach. The data collection method used observation, interviews, documentation, and a literature study. While the data analysis technique is descriptive and qualitative by reducing data, presenting data, and drawing conclusions. The results showed that the Peta kapanca tradition at the wedding ceremony of the Bima tribal community in the Ambalawi sub-district contained local wisdom values ​​in the form of faith values, brotherhood values, mutual help values, and patient values. The values ​​of local wisdom in the Peta kapanca tradition align with Islamic law, namely, having values ​​that do not conflict with Islamic teachings. This made local wisdom in the Peta kapanca tradition and Islamic teachings valuable as instruments in developing Islamic da'wah teachings. In addition, socio-culturally as a bulwark against the modern era in the form of globalization and liberalization due to the influence of outside culture, which is starting to erode. Keywords: Local culture, Islamic law, Peta kapanca, wedding